Empowering marginalized communities through the digital transformation course - Yüksel-Arslan, Pelin; Plant, Claudia; Kayali, Fares (Frontiers in Education, 2025)
This article examines a project dedicated to comprehensively addressing the social impact of digital transformation. The project also emphasizes the effects of digital transformation on marginalized populations, especially forced migrants and individuals with special needs. The project involves the development of open-access course materials titled “Digital Life 1–2–3-4,” which are shared as open-access resources through four MOOCs on the iMooX platform. The primary goal is to increase awareness of the effects of digital transformation in daily life, such as algorithmic bias, inaccessibility, robots and digital divide, digital inclusion, and digital discrimination. By integrating ethical considerations, promoting digital literacy, and considering bringing users into the design process, the course mitigates the impact of digital transformation and promotes an equitable and empowering digital environment for the everyday use of technology, particularly for marginalized communities. In this article, we discuss specific course content, including digital inclusion, algorithmic bias, and emerging inequalities. The key goals are to understand and mitigate the risks of algorithmic bias, inaccessibility, and digital discrimination in educational technologies affecting diverse and vulnerable populations, and to promote digital literacy, access, and motivational design to encourage forced migrants’ active and safe participation in technology-enabled education. We conclude that it is essential to prioritize ethical principles in their design and application, elevate underrepresented voices, and foster a more equitable and inclusive digital landscape.